COVID-19 knowledge, attitude, and preventive practices among government and private bank workers in Ethiopia - Hassen, Seada; Adane, Metadel (Frontiers in Public Health, 2023)
Background: Bank workers are among the many servicesector employees who are at risk of COVID19 infection. Individual's adherence to control measures is affected by their COVID19 knowledge, attitudes, and practices (KAP). Since KAP is an important cognitive key in public health prevention and promotion, this study aimed to identify COVID19 KAPrelated gaps among bank workers in Dessie City, Ethiopia and to guide banks and health authorities in taking corrective actions.Methods: An institutionbased crosssectional study was conducted from January 1 st to 30 th , 2021 among 413 bank workers. A binary logistic regression was applied to determine association of independent variables with outcome variables using three different models. Variables at 95% confidence interval (CI) with a pvalue <0.25 from bivariate analysis were transported to three different multivariable logistic regression models and then variables with a pvalue of 0.05 from the multivariable analysis of each model were declared as significantly associated with the outcome variables.: The results of this study show that 84.7% [95% CI: 81.188.1] of bank workers had good knowledge, 50.4% positive attitude, and 50.6% [95% CI: 45.855.0] good practice towards prevention of COVID19. The only variable significantly associated with knowledge in this study was positive attitude (AOR = 8.89; 95%CI: 3.3423.64). Being ≥35 years old (AOR = 2.46; 95%CI: 1.254.84) and getting information on COVID19 (AOR = 3.81; 95%CI: 1.84 7.91) were among factors significantly associated with attitude towards COVID19 prevention, whereas being female and ≥35 years old (AOR = 2.56; 95%CI: 1.295.06) and (AOR=2.73; 95% CI: 1.156.51), respectively were factors associated with good preventive practice towards 3 COVID19. Conclusion and recommendation: considering those significant factors responsible for determining COVID19 KAP level of respondents, health education program and information dissemination are recommended, including appropriate strategies by policy makers and bank managers to develop effective interventions for COVID19 transmission in banks.